Diseño de planta para la clasificación y transformación de residuos sólidos aprovechables en la comuna 6 del municipio de Neiva - Huila. - Bernal Salgado, Juan Diego (Universidad Antonio Nariño, 2023)
In the capital of the Huila departamento, in Neiva, different environmental problems can be evidenced in relation to the management and inadequate treatment of solid waste, especially usable inorganic solid waste. This is due to the companies providing the station, classiication and use service. Where these companies have irregularities is the infrastructure and does not allow them to be aligend with the regulations. That is why the objective of this research is to carry out the architectural design proposal (ECA) for the collection and use of them in the city of Neiva; this infrastructure is shown as a viable projection to significantly improve the use of inorganic solid waste and cause a reduction in solid waste that reaches the Los Angeles landill in the city of Neiva- Huila. The research approach is carried out through a qualitative approach, whre it seeks to explain the main causes and effects that arise from nom.compliance with the service provider companies, this goes hand in hand with the desinterest and lack of sense of belonging on the part of citizens when carrying out the proper separation and classification of waste.